Implication of Tityus apiacas (Lourenco, 2002) in scorpion envenomations in the Southern Amazon border, Brazil - Bruna Andressa Jung da Silva; Nelson Ferreira Fé; André Alexandre dos Santos Gomes; Anderson da Silva Souza; Jacqueline de Almeida Gonçalves Sachett; Hui Wen Fan; Gisely Cardoso de Melo; Wuelton Marcelo Monteiro (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract Herein, four cases of scorpion stings caused by Tityus apiacas recorded from the municipality of Apuí, in the southern region of the Brazilian Amazon, are described. Patients showed systemic clinical manifestations, described as unusual, involuntary, and generalized tingling and numbness, reported by patients as an electric shock sensation, lasting up to 24 hours after the sting. All patients described local pain and sensation, along with other clinical symptoms including local edema and erythema. Systemic manifestations were not life threatening. Antivenom therapy was administered to all patients, who were discharged without complaints.